The world market of the wine sector - Petruţa Antoneta Enache (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
The increased share of horticultural crops in the world economy of agricultural production is due to the role that grapes, fruits and vegetables have in the rational nutrition of man and in increasing the national income of the cultivating countries, as well as in improving the microclimatic living conditions of of man. Viticulture, held and holds a well-defined place in the agricultural economy and the national economy, whose importance can be appreciated from several points of view. The research is based on data provided by the National Institute of Statistics and OIV regarding the area of vines intended for the production of wine grapes, table grapes or dried grapes, the production and consumption of wine by traditional producers and the trade of the producing countries of the world with an emphasis on the period 2018-2022. The following research methods were used in the elaboration of this research: monograph, analysis and synthesis with the help of statistical indicators.
Keywords: Q10; Q12; Q14; Q19; 330; viticulture; production; consumption; trends